Religious Experience: Hierophany or Hierophony - Vidauskytė, Lina (Religija ir kultūra, 2012)
The human sensorial system in oral society and tradition is oriented differently than in visual culture. Priority is given to voice and to the rhythmical property of the auratic organ of sense. Such sensorial combination is necessary in all areas of oral society and its culture. Voice plays one of the most important roles in religion. God addresses the human, and the human appeals to God. Yet this basic auratic religious experience was displaced by written culture. Thus, the main question of this paper is the suitability of term “hierophany” (which is widely used in religious studies) for naming the specificity of religious experience.
Keywords: hierophany; hierophony; orality; voice; sacrum